KOMUNITAS VEGETASI PIONIR DAN PERKIRAAN AKUMULASIBIOMASSA PADA LAHAN GAMBUT BEKAS TERBAKAR DI AREA TRANSISICAGAR BIOSFER GIAM SIAK KECIL – BUKIT BATU RIAU - Dien Septiani; Haris Gunawan; Nery Sofiyanti (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
After-burned peatland formed a new pioneer vegetation communities for biomass stored. In the next process, this vegetation reduce carbon emission into the air which caused by the releasing of stored carbon in natural peatland. The purpose of this research is to know the characteristics of natural succession in the early stage of pioneervegetation communities in after-burned peatland. Total biomass accumulation was counted using allometric equation BP = 0,1236 D2,3677, Wtotal= 0,1531080 (D)2,40, Btotal = 0.1923 D2.15, M = 7.50 × 10–2(D)2.60 dan M = 1.49 × 10–1(D)2.09 . The pioneer vegetation which were observed after the peatland fire were tenggek burung (Euodia sp.), kayu ara (Ficus sp.), mahang (Macaranga triloba), karet (Havea brasiliensis), sendayan (Scleria sumatrensis), alang–alang (Imperata cylindrica), senduduk (Melastoma malabathricum), paku-pakuan (Neprolepis hirsutula) dan rumput teki (Cyperus rotundus). The abundance of woody vegetation, Euodia sp., become very dominant after the first stage of successionin after-burned peatland. Total surface biomass accumulation from the beginning of succession in all types of pioneervegetation was338,91 kg/ha/years.